Spontaneous Supraceliac Isolated Abdominal Aortic Dissection Sparing Major Visceral and Renal Vessels and Presenting as Chronic Limb Ischemia - Sean O. Z. Bello; Ilias Kouerinis; Woolagasen Pillay (International Journal of Vascular Medicine)
Aortic dissections that originate from isolated tears in the abdominal aorta are uncommon. Rarer still are cases of isolated abdominal aortic dissections arising in suprarenal locations, as most appear from infrarenal intimal defects. We present a quite unusual case of a spontaneous supraceliac isolated abdominal aortic dissection sparing the renal and mesenteric arteries and manifesting as chronic rather than acute limb ischemia. The atypical presentation of this case led to repeated misdiagnosis with consequent loss of part of the patient's limb. Better illustration of the natural history of this ill-defined pathology is needed to aid understanding and improve patient care.